The Impact of Endometriosis Diagnosis on Women’s Mental Health-A Cross-Sectional Study: Endometriosis Diagnosis on Women’s Mental Health - Hameed, Sajid; Shafique, Muzamal; Anjum, Zartashia; Tahseen, Huma; Mannan, Amna; Butt, Nazia Ayyub; Shafique, Nimra; Tariq, Aqsa (Pakistan Journal of Health Sciences, 2024)
Endometriosis is a chronic condition where tissue similar to endometrium grows outside the uterus. It affects the social and psychological life of women. Objective: To evaluate the impact of endometriosis diagnosis on women’s mental health. Methods: In this cross-sectional study basal data, Endometriosis Health Profile (EHP-30) statuses, and Hospital Anxiety and Depression scale scores were collected from 200 sub-fertile women who were sampled using a non-probability sampling technique. Frequency distribution and chi-square (X2) analysis were performed using IBM SPSS® version 26.0. Results: Out of 200 sub-fertile women 28 (14%) had endometriosis. Positive endometriosis significantly correlated with age (0.09<0.1). The endometriosis-related health statuses significantly correlated with anxiety and depression with two-sided asymptomatic significances of 0.007 (<0.05) and 0.000 (< 0.05) respectively. The highest prevalence of severe anxiety and depression was present in women with bad possible health profiles related to endometriosis. Conclusions: It was concluded that endometriosis aggravates with age and its positive diagnosis has a strong negative impact on the social and psychological health of the patients.